re:generation Europe - de Witte, Floris. author. aut Link
IX, 141 p. 2 illus. in color.
Keywords: This book sets out a vision for another Europe: one that cherishes diversity, listens to its public, and is sensitive to its younger generations. It is a call for a re-imagination of the European project, as a response to the three biggest crises that the EU has had to endure – the Euro-zone crash, the refugee crisis, and Brexit. These crises demonstrate a fundamental weakness at the heart of the EU: it struggles with making legitimate decisions when member states disagree about how to proceed. This book offers a guide out of this mess. It discusses how the EU can make better use of the trust between its citizens, and how it can reform itself internally so that it can actually listen to those citizens. It also offers ten original policy proposals – from the scandalously ambitious to the prosaic – to show what another Europe could look like. Floris de Witte is Associate Professor in the Department of Law at the London School of Economics and Political Science, UK.